HUBUNGAN PELATIHAN DENGAN PERILAKU BIDAN DALAM MELAKUKAN PENCEGAHAN PENDARAHAN POSTPARTUM DI KABUPATEN BANTUL - Diah Nur Anisa; Detty S Nurdiati; Wiwin Lismidiati (MEDIA ILMU KESEHATAN, 2019)
Background: Postpartum hemorrhage is define as 500 cc or more bleeding after the completion of third stage (after the placenta is born). Maternal mortality due to postpartum hemorrhage occurs a lot in health services, one of the factors that influence it is the behavior of health workers in the prevention of postpartum hemorrhage. The behavior of midwives in preventing postpartum hemorrhage is closely related to the competencies seen from the training attended. Objective: To find out the relationship between training and the behavior of midwives in preventing postpartum hemorrhage in Bantul Regency. Methods: We used a correlation study with a cross sectional design. The sampling technique in this study used probability sampling with cluster sampling totaling 68 midwives in five community health centers. Retrieval of data in this study used an observation sheet to see the actions of midwives in conducting active management in the third stage as a preventive measure for postpartum bleeding and the identity sheet of respondents to see the training that had been attended by midwives. Results: There was no relationship between training with the behavior of midwives in the prevention of postpartum hemorrhage in Bantul Regency with a p value of 0.093. A total of 40 midwives (58.8%) had good behavior and 53 midwives (77.9%) had attended training. Conclusion: There is no training relationship with the behavior of midwives in the prevention of postpartum hemorrhage in Bantul Regency Keywords: Behavior, hemorrhage, postpartum, training